2009
DOI: 10.1159/000252798
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-Associated Occlusion of the Internal Carotid Artery

Abstract: Background: Cisplatin is a highly effective antineoplastic agent used also in germ cell cancer. Thromboembolic complications like pulmonary embolism, myocardial infarction and stroke have occasionally been reported. Case Report: A 46-year-old man with seminoma and without any cerebrovascular risk factors developed an acute stroke with complete right-sided hemiparesis and global aphasia, during the second cycle of cisplatinbased chemotherapy. After exclusion of an intracerebral bleeding, a systemic thrombolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…Studies in the literature show that the risk of ischemic stroke in chemotherapy does not appear to be related to the type of cancer but to the type of drug used [3,4]. Thus, in the cases reported the most incriminated drugs were cisplatin [5][6][7][8] which comes in 1st position and 5-Fluorouracil (5FU). Both were used in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the literature show that the risk of ischemic stroke in chemotherapy does not appear to be related to the type of cancer but to the type of drug used [3,4]. Thus, in the cases reported the most incriminated drugs were cisplatin [5][6][7][8] which comes in 1st position and 5-Fluorouracil (5FU). Both were used in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Since a CRS in patients without the conventional stroke etiology is characterized by the elevation of D-dimer levels and the presence of microembolic signals detected by transcranial Doppler, its etiological mechanism is mainly regarded as an embolism caused by hypercoagulopathy (1,4,5). In contrast, cases of a CRS that produces a thrombus in a large vessel have rarely been reported, and in most of them, cisplatin-based chemotherapy was administered (2,(6)(7)(8)(9)(10). Thrombus formation is assumed to be due to vascular toxicity associated with cisplatin, including induced endothelial damage and increased platelet aggregation (11), as well as hypercoagulopathy due to cancer itself.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, cases of CRS due to a large vessel thrombus have only rarely been reported. In most of them, cisplatin-based chemotherapy as well as cancer itself contributed to the thrombus formation (2,(6)(7)(8)(9)(10). We herein report a patient presenting with ischemic stroke due to a thrombus of the extracranial carotid artery complicating metastatic colorectal adenocarcinoma.…”
Section: Introductionmentioning
confidence: 91%
“…It has been reported that there is a high incidence of cardiovascular events in survivors of cisplatin-based chemotherapy cancer patients (25), either in acute or long-term chemotherapy (26,27). Cisplatin was reported to lead to aortic occlusion in some cases and this impairment was usually irreversible (28,29). In one case, a 36-year-old man who was treated with bleomycin-etoposide-cisplatin therapy for testicular cancer received chronic coronary artery dissection (30).…”
Section: Discussionmentioning
confidence: 99%